Opportunities for Mitigating the Environmental Impact of Energy Use in the Middle East and North Africa Region - Zhang, Yabei (World Bank, Washington, DC, 2014)
The main motivation for Middle East and North Africa Region (MENA) governments to improve energy efficiency is to address pressing domestic concerns, such as urban air pollution, energy security, economic competitiveness, the fiscal cost of energy subsidies and the balance of payments. However, improved energy efficiency is also seen as the most promising route for reducing the region's green house gas (GHG) emissions. Therefore, as part of the study on energy efficiency in MENA, this report aims to describe and quantify the links between energy efficiency and GHG emissions as well as urban air pollution in MENA. More specifically, the objectives of the report is: (i) to create scenarios of emissions of GHG and selected urban air pollutants (specifically, particulate matter (PM)) under different assumptions of energy efficiency improvements; (ii) to identify the country/sectors where energy efficiency improvements are likely to have the greatest impact upon GHG and PM emissions; and (iii) to benchmark MENA against other regions in terms of energy intensity and GHG emissions.